Consensus? An Examination of Differences in Earnings Information Across Forecast Data Providers - Larocque, Stephannie; Watkins, Jessica; Weisbrod, Eric (Journal of Accounting Research, 2026)
ABSTRACT We compare the earnings information produced by the five largest forecast data providers (FDPs)—Bloomberg, Capital IQ, FactSet, I/B/E/S, and Zacks—and observe substantial differences across FDPs in both forecasted and actual street earnings values, and thus the earnings surprise, for the same firm‐quarter. We provide evidence that differences in the earnings surprise across FDPs for the same firm‐quarter (i.e., “FDP differences”) have economically meaningful implications for price responsiveness and liquidity around earnings announcements. We also find that, for announcements where FDPs disagree about whether the announcing firm missed or beat earnings expectations, investors are more likely to side with higher‐quality FDPs but may not fully impound the implications of FDP quality differences during the announcement window. On average, relative to the other FDPs, I/B/E/S ranks highly in our measure of FDP quality, such that investor reactions are likely to align with I/B/E/S earnings information, validating its use as a representative FDP in academic research. Taken together, our results are consistent with FDPs pursuing differentiated information production strategies that generate capital market frictions when these strategies lead to material FDP differences.